Desarrollo postembrionario de Latrodectus variegatus (Araneae: Theridiidae) - González, A (1998)
The Iife cicle of Latrodectus variegatus from cocoons collected in Bariloche, Argentina, is described. In stage IV (first free stage) 361 individually bred spiders were isolated and fed Drosophila melanogaster in the juvenile stage and Musca domestica after wards. "Stage 1" is the stage following eclosion. For the study of survival, and average Iife expectancy, a week wa